Nerve Growth Factor Homology in the Nerve Regeneration-Conditioned Fluid of Rabbits and Rats - Ye, Y.; Li, Q.F.; Li, L. (Нейрофизиология, 2015)
We analyzed the homology of nerve growth factor (NGF) in the nerve regenerationconditioned fluid (NRCF) obtained from New Zealand white rabbits and SD rats. A nerve regeneration chamber bridged distal and proximal ends of the severed rabbit sciatic nerve, and the NRCF was extracted from such chamber. The supernatants and precipitates of nerve tissue of rabbits and rats were extracted from the sciatic nerves by grinding and centrifugation. An antigen-antibody reaction was detected by the ELISA technique using rabbit anti-mouse NGF as primary antibody and goat anti-rabbit IgG as secondary antibody. Antigen-antibody reactions were detected in all the above-mentioned samples obtained from rabbits and rats. The intensity rank of an antigen-antibody response for different samples was the following: rabbit NRCF > rabbit nerve tissue precipitation fluid > rabbit nerve tissue fluid supernatant > > rat nerve tissue fluid supernatant. Thus, there is high homology of the molecular structure of NGF in the NRCFs obtained from rabbits and rats (i.e., animals belonging to different taxonomic groups of mammals).